A climate justice perspective on international labour migration and climate change adaptation among Tuvaluan workers. Issue 1 (11th March 2022) - Farbotko, Carol; Kitara, Taukiei; Dun, Olivia; Evans, Christopher
Abstract: Research on climate change and human mobility has posited migration as a potentially adaptive response. In the Pacific Islands region, international labour migration specifically is an important component of emerging climate change mobility policy, at both regional and national scales. However, the existence of opportunities for people in climate-exposed locations to move for work does not, on its own, advance climate justice. To gain insights into the nexus of climate justice, labour migration and adaptation, this paper explores the social and emotional experiences of international labour migration programme participants from climate-vulnerable Tuvalu as well as the emergent climate mobility regime in which this migration is taking place, drawing on qualitative research undertaken on the policy context and with workers from Tuvalu on short-term contracts under Australia's Pacific Labour Scheme. Their experiences, their perceptions of climate change and their role as livelihood earners for families are explored to consider issues of climate justice in understanding labour migration as adaptation. While the workers benefited economically, they experienced significant social and emotional issues including poor mental health and family breakdown during their time working abroad, in addition to long-term climate change concerns. Further, the labour mobility programme in which they participated does not recognize migration-as-adaptation or climate justice, even though these are an emergent priority in the climate mobility regime. This highlights the need to consider how international labour migration programmes can be strengthened to advance climate justice for climate vulnerable populations on the move.